Japan Theme Park Di Pekanbaru Dengan Pendekatan Arsitektur Tradisional Jepang - Astri Larasti; Ratna Amanati; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Recreation is one thing that needed by the community, include the people in Pekanbaru City. Pekanbaru is developted city. The media that can accommodate the needs of leisure and entertainment for all society is theme park. Japan Theme Park is designed with the concept Japanese culture. Themes and concepts have to be related to Japan in addition to enjoying recreation and entertainment. Visitors can also learn about positive values such the culture of Japan. Japan is the country that has historical links with Indonesia. Japanese culture is shown into Japan Theme Park, grouped and limited to produce any buildings that will be displayed at the Japan Theme Park. Japanese traditional architecture incorporated into the design of Japan Theme Park through the application of some characteristics of Japanese traditional architecture. The direction of building orientation, mass order, building mass formations, building facades, building structure, and interior of the building are the application of some characteristic of Japanese traditional architecture. The approach was applied to all elements of design, ranging from outdoor fabric, formed by the masses, up to the room within Japan Theme Park. With the application of Japanese culture as a concept and Japanese traditional architecture as a theme could cause a great atmosphere of Japan in ancient times. Visitors who come to Japan Theme Park will be persuaded to enjoy the Japanese culture, accompanied by Japanese traditional architecture.Keywords: Japan Theme Park, Japanese Culture, Japanese Traditional Architecture